Effect of Various Rapid Cooling Treatment on the Structural Properties of Iron Nickel Aliminium Alloy Deposited by Detonation-Gun (D-Gun) Method - Masbah R.T. Siregar; Gerald E. Timuda; Farid W. Machmud; Muchiar Muchiar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2011)
Iron base alloy such as iron aluminide (Fe-Al) is known as corrosion resistance material at elevated temperature. Addition of chromium and nickel to the material can increase the temperature capability. Deposition of Fe38Ni10Al alloy material has been done by using D-Gun method on Stainless Steel substrate. One of the characteristics should be evaluated is the crystalline structural properties of the alloy. It is known that nanocrystalline or amorphous structure is preferable as they are able to increase the mechanical properties. Rapid cooling treatment of the alloys from its molten state is done to give different chemical and mechanical properties, to achievenanocrystalline structure. This treatment was carried out by rotating the substrate and simultaneously rotating and spraying distilled ice-water to the substrate throughout the deposition process. From the XRD pattern of the deposited alloys, there can be seen the occurrence of phase transformation compared to as-received alloy. The -(Fe,Ni), FeNi3 and Al phase of as-received alloy were changed into only -(Fe,Ni) phase of deposited alloys. The apparent crystal size evaluated by Scherrer Method was in nanometer scale size. The successivespraying of distilled ice-water gives effect on the decrease of crystal size of the deposited alloy (37.78 nm) as compared to non-sprayed deposited alloy (56.80 nm).